Outcome measures in randomized controlled trials of neuropathic pain conditions: a systematic review of systematic reviews and recommendations for practice - Meeta, Poonam; Claydon, Leica; Hendrick, Paul; Winser, Stanley; Baxter, G. David (Lippincott, Williams & Wilkins, 2015)
Objectives: Neuropathic pain (NeP) is a prevalent, disabling, multi-dimensional condition with significant morbidity; however there appears to be a variable approach in the use of outcome measures in NeP trials. A search of systematic reviews of interventional randomized controlled trials for NeP was undertaken to investigate the range and types of outcome measures employed to determine treatment effects. Methods: Keywords and MESH searches were conducted in five electronic databases from inception to 31st January 2012. Full text English language reviews based on various acute and chronic NeP conditions were included. Two independent reviewers screened papers for inclusion, extracted data, and assessed the quality of reviews. Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines were used to critically appraise the reviews. Results: A total of 46 studies were identified: the majority of reviews (n=28/46, 61%) scored well on the PRISMA (PRISMA scores of 20-27/27). Change in levels or intensity of pain were used by the majority of studies as the primary outcome measure in intervention studies (n=40/46 studies, 87%). Few studies employed a functional outcome measure (FOM) as either a primary or secondary outcome measure (n=7/46, 15% of studies). Discussion: These results demonstrate that measures of pain are predominantly used in trials of NeP conditions and highlight the scant usage of FOMs. The lack of standardization for the diagnostic criteria in NeP trials is also an issue which needs to be considered for future research and guideline development.